Effects of a cold plasma-assisted shrimp processing chain on biochemical and sensory quality alterations in Pacific white shrimps (Penaeus vannamei). (December 2022) - Elliot, Mubango; Chen, Jing; Chen, Dong-zhi; Hu, Xiao-meng; Ekaterina, Nikolaeva; Deng, Shang-gui
In this paper, remodeling the shrimp processing chain and the effects of the transformation on the biochemical and sensory qualities of fresh Pacific white shrimp ( Penaeus vannamei ) under refrigeration storage were investigated. In the proposed model, a dielectric barrier discharge atmospheric cold plasma pretreatment step using a 60 kV source for 60, 90, 120, and 150 s was introduced after the first and second wash followed by refrigeration storage at 4 ± 1 °C for 12 days. Chemical, biochemical, and sensory attributes of the shrimp were monitored and compared with those of shrimp processed through the traditional method without atmospheric cold plasma pretreatment (control). Incorporating minimal dielectric barrier discharge atmospheric cold plasma pretreatment step had more desirable quality outcomes characterized by low malondialdehyde concentration, low volatile nitrogen products content, and comparable proximate composition. Texture, pH, and color were remarkably retained at 120 and 150 s of atmospheric cold plasma pretreatment and protein degradation was negligible up to 90 s than at 120 and 150 s of pretreatment. We conclude that remodeling the shrimp processing chain through incorporating minimal dielectric barrier discharge atmospheric cold plasma pretreatment with key considerations on operation parameters can maximize the beneficial biochemical and sensory quality outcomes while minimizing the negative impacts associated with traditional shrimp processing.